Review of Research on Dynamic Characteristics of Rolling Bearing Cages - Pan, Chengyi; Li, Shuhao; Zhang, Jingren (Recent Patents on Engineering, 2025)
BackgroundRolling bearings are being widely used in various applications because of their unique functions, but at the same time, bearing failures are becoming more and more prominent. Among them, the bearing failure caused by cage failure also accounted for 25% of the total proportion. With the progress of intelligent manufacturing and “Industry 4.0”, the operating environment of rolling bearings is becoming increasingly complex and variable, and higher demands are made on the dynamic characteristics of cages. In this regard, the research on the nonlinear dynamics of the cell under different influencing factors can help to explain better the mechanism of dynamic, unstable motion of the cage under various influencing factors and solve the bearing life and reliability problems caused by uneven rolling bearing cage from the perspective of design and experimental research.ObjectiveBy summarizing the influencing factors of cage dynamics characteristics, the design of new structures, test methods, and testing devices of dynamics attributes in recent years, some valuable conclusions were obtained, and the future development direction of rolling bearing cage dynamics characteristics was proposed to provide a reference for researchers in related fields.MethodsThis paper reviews the patents and documents related to the dynamic characteristics of rolling bearing cages, as well as analyzes the different influencing factors on the operational stability of the bearings, and introduces the improved design of cage structures, as well as the test methods and testing devices for the dynamic characteristics of cages.ResultsThrough the analysis of relevant patents and papers on rolling bearing cage dynamics, the development status and problems of rolling bearing cage dynamics were discussed, future research on rolling bearing cage dynamics was prospected, and design ideas and research directions were proposed.ConclusionThrough the discussion of the factors influencing the cage dynamics, the optimization of the rolling bearing cage structure design, and the study of test methods and testing devices, it was found that the research direction of the rolling bearing cage dynamics needs to be further expanded so that a better research method and testing devices could be researched, and a new structure with more stable operation and higher cage life and reliability could be designed.
Keywords: cage